Assessment of Guneid Sugar Factory social impacts - M. A. Elzebair, Selwa Ahmed; Ahmed, Mudather Ali; Elamin, Abbas Elsir M. (Gezira Journal of Agricultural Science; Vol 14 No 2 (2016), 2016)
ABSTRACT  Sugar is one of the most important and oldest commodities in the world. In the Sudan, there are two types of sugar estates; public and private. Sugar industry in the Sudan is one of the  important and effective industries for the Sudanese economy. In addition, sugar cane production schemes in the Sudan are very effective with regard to community development and wealth distribution. The objective of this study was to assess the social impacts of Guneid Sugar Factory which is a public and first sugar factory in the Sudan. Like other sugar factories, Guneid Sugar Factory has a significant role in the Sudan economy, as well as in the social development of the area.  This factory differs slightly from all sugar factories in Sudan, because it operates by tenants who belonged to Gezira Scheme before the establishment of the factory. The study used primary data through a questionnaire with a random sample from Guneid tenants and used descriptive statistics for analysis. The study showed that the scheme substantially contributed to the establishment of schools, health centers, hospitals, provision of electricity, healthy drinking water and increased the income of inhabitants. The study concluded that, Guneid is providing excellent social services that have apparent contribution to the improvement of the livelihood of the communities.